Rare presentation of transposition of great arteries and total anomalous pulmonary venous connection in an 18‐year‐old. Issue 10 (12th September 2021) - Chatterjee, Debika; Gangopadhyay, Debasree; Narayan, Pradeep
Abstract: Transposition of great arteries (TGA) in association with total anomalous Pulmonary venous connection (TAPVC) is a rare anomaly, that is seldom reported in adulthood. While both the conditions are life threatening on their own, in combination they compensate for each other and can often present after weeks or months after birth. Transthoracic Echocardiography (TTE) can reliably diagnose this anomaly. Cardiac MRI can also be used to confirm the diagnosis. We describe a rare combination of TGA and TAPVC in an 18‐year‐old patient.